Er3+-to-dye energy transfer in DNA-coated core and core/shell/shell upconverting nanoparticles with 980 nm and 808 nm excitation of Yb3+ and Nd3+. Issue 7 (11th February 2020) - Francés-Soriano, Laura; Peruffo, Nicola; Natile, Marta Maria; Hildebrandt, Niko
Abstract : FRET from upconversion nanoparticles to dyes using 980 nm and 808 nm excitation. Abstract : The capability of upconverting nanoparticles (UCNPs) to convert near infrared (NIR) into visible light has become an important feature for biosensing, imaging, therapy, and their combination. While significant achievements have been accomplished during the last decade developing nanohybrids based on UCNPs as energy donors in Förster resonance energy transfer (FRET) systems, it is still challenging to understand and control FRET from UCNPs to dyes and to adapt the NIR excitation wavelength. Here, we describe the synthesis, characterization, and steady-state and time-resolved FRET analysis of UCNP–DNA nanohybrids, in which dye labelled single stranded (ss)DNA was attached to Yb–Er-co-doped core UCNPs (c-UCNPs) and c-UCNPs with a thin Nd-doped shell and a second thin undoped shell (css-UCNPs). Despite differences in sizes, compositions, donor–acceptor distances, brightness, and excitation wavelength (980 nm for Yb 3+ and 808 nm for Nd 3+ ), all UCNP–DNA nanohybrids showed very similar concentration dependent FRET-quenching of UCNP luminescence with efficiencies between 0 and ∼20%. We analyzed luminescence intensities, decay times, and rise times and could show the entanglement of excitation and emission kinetics by simply changing the excitation wavelength from 980 nm to 808 nm for the same css-UCNPs. Time-gated FRET-sensitized dye luminescence showed dye-ssDNA concentration dependence over four orders of magnitude (1 nM to 10 μM), which suggested a possible application to nucleic acid biosensing for both 808 and 980 nm excitation.